THE INFLUENCE OF SCIENCE LEARNING SET USING SCIENTIFIC APPROACH AND PROBLEM SOLVING MODEL ON LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS IN THE SUBJECT OF HEAT AND TEMPERATURE - Triyuni, T. (Jurnal Pendidikan IPA Indonesia, 2016)
This research aims to produce the scientific approach for science learning using a problem solving model on the topic of heat and temperatureon the junior high school learning outcome. The curriculum used during the study was curriculum 2013 (valid, practical and effective). The development of the learning setfollowed the four-D model which was reduced to three-D model (without dissemination). The study was tested in Class VIIA, VIIB, and VIIC in SMP Negeri 5 Academic Year 2015/2016. The data collection technique employed the validation of the learning set, observation, testing, and questionnaire. The results of study show that the developed learning set has a decent (valid, practical, and effective). The competency in learning outcomes show N-Gain in high level with the average value ranged between 0.80 to 0.86. The impact of learning on three classes were tested by ANOVA on 0.05 significance level to produce F value â¤F table, meaning that there is no difference in the impact of learning on threeclasses with consistent value. The student competence skills anddemeanors, the skills of each category showed good and positive response to learning. The research concludes that the scientific approach for science learning using a problem solving model is suitable for learning application (validity, practicality, and effectiveness).By mastery in learning management, the learning objectives can be achieved smoothly.